Genome Sequencing of Extended-Spectrum β-Lactamase (ESBL)-Producing Klebsiella pneumoniae Isolated from Pigs and Abattoir Workers in Cameroon - Founou, Luria L.; Founou, Raspail C.; Allam, Mushal; Ismail, Arshad; Djoko, Cyrille F.; Essack, Sabiha Y. (Frontiers in Microbiology, 2018)
Background and objectives: Extended-spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae is a serious public health issue globally. In this study, the antibiotic resistance genes, virulence factors, mobile genetic elements and genetic lineages of circulating ESBL-producing K. pneumoniae strains isolated from pigs and humans in Cameroonian abattoirs were investigated using whole genome sequencing (WGS), in order to ascertain zoonotic transmission (viz. from animals to humans and/or vice-versa) in the food chain. Methods: During March–October 2016, 288 nasal and rectal pooled samples from 432 pigs as well as nasal and hand swabs from 82 humans were collected from Cameroon and South Africa. Seven ESBL-producing K. pneumoniae circulating in Cameroonian pig abattoirs were selected and their genomic DNA sequenced using an Illumina MiSeq platform. Generated reads were de novo assembled using the Qiagen CLC Genomics Workbench and SPAdes. The assembled contigs were annotated using RAST and antibiotic resistance genes, virulence factors, plasmids and bacteriophages were identified with ResFinder, Virulence Finder, PlasmidFinder and PHAST, respectively. Results: ESBL-producing K. pneumoniae were detected in pigs (34/158; 21.52%) and exposed workers (8/71; 11.26%) in Cameroon only. The circulating K. pneumoniae strains were dominated principally by the sequence type (ST) 14 and 39. In addition, the “high-risk” ST307 clone and two novel STs assigned ST2958 and ST2959 were detected. Genomic analysis identified various antibiotic resistance genes associated with resistance to β–lactams, aminoglycosides fluoroquinolones, macrolide, lincosamide and streptogramins, rifampicin, sulphonamide, trimethoprim, phenicol and tetracycline. None of the ESBL-producing K. pneumoniae harbored virulence genes. Intermingled K. pneumoniae populations were observed between pig- and human-source within and across abattoirs in the country. Conclusion: Our study shows that ESBL-producing K. pneumoniae is actively disseminating in pigs and occupationally exposed workers in Cameroonian pig abattoirs and is probably underestimated in the absence of molecular epidemiological studies. It suggests pigs, abattoir workers and food products as potential reservoirs and sources of zoonotic transmission in Cameroon. Our findings underline the existence of a potential unheeded food safety and public health threat associated with these resistant strains and reinforce the crucial importance of implementing appropriate food safety measures and promoting rational antibiotic use.